2022-RA-649-ESGO Response to treatment and prognostic significance of supradiaphragmatic disease in patients with high-grade serous ovarian cancer. (20th October 2022) - Roberti Maggiore, Umberto Leone; Bogani, Giorgio; Martinelli, Fabio; Signorelli, Mauro; Chiappa, Valentina; Lopez, Salvatore; Ditto, Antonino; Raspagliesi, Francesco
Abstract : Introduction/Background: This study was designed to investigate the response to chemotherapy of supradiaphragmatic disease diagnosed by preoperative imaging. As secondary objectives, oncologic outcomes of patients affected by supradiaphragmatic disease and their pattern of recurrence were also evaluated. Methodology: Data of consecutive patients with newly diagnosed FIGO stage IV (for supradiaphragmatic disease) epithelial ovarian cancer undergoing either primary debulking surgery or neoadjuvant chemotherapy plus interval debulking surgery between 2004 and 2021, were retrospectively collected. All patients were preoperatively evaluated by chest/abdominal CT scan or 18 F-FDG PET/CT preoperatively and at follow-up to evaluate response to chemotherapy. At follow-up visits, site of recurrence diagnosed by imaging techniques was systematically recorded as it occurred. Progression-free and overall survival were measured by using Kaplan-Meier and Cox models. Results: A total of 130 patients was included in this study with a median (range) follow-up of 32.9 (12.8–176.7) months. Complete or partial response was achieved in most of the patients after 3 cycles (77.7%) and 6 cycles (85.4%) of chemotherapy. At follow-up, recurrence occurred in 96 (73.8%) patients and the main site of recurrence was abdomen only in 64 (66.7%) patients. At multivariate analysis, residual disease after surgery was the only variable influencing survival outcomes. Conclusion: Supradiaphragmatic disease respond to chemotherapy in most patients affected by advanced EOC and recurrence mainly occurs in the abdomen. Results from this study confirms that abdominal optimal cytoreduction is the main surgical goal in the treatment of women affected by FIGO stage IV EOC.